ADAB SEBAGAI FONDASI FILOSOFIS PENGEMBANGAN KECERDASAN INTELEKTUAL SISWA SEKOLAH DASAR: SEBUAH KAJIAN LITERATUR - Khairani, Intan; Karneli, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes adab as a philosophical foundation for developing intellectual intelligence in elementary school students. Using a systematic literature review method, this study examines 31 scientific articles relevant to the themes of adab, intellectual intelligence, and elementary education. The findings show that adab, as conceptualized by Al-Attas, Al-Ghazali, and Wan Mohd. Nor Wan Daud, constitutes an epistemological condition that determines a student's readiness to receive and internalize knowledge. In the context of elementary school students in the concrete operational stage (ages 6-12), early cultivation of adab significantly impacts the quality of learning processes and outcomes. Pedagogical implications affirm the urgency of holistic adab integration in curriculum, teaching practices, and school culture.